Semiotics Analysis of Modern Drink Advertisements on the Palangkaraya Cafe Instagram Account - Sutiah; Imam Qalyubi; Zaitun Qamariah (Pendidikan Bahasa Inggris Universitas Nurul Huda, 2023)
This research paper titled